History of Concepts Comparative Perspectives - Hampsher-Monk, Iain; Tilmans, Karin; Vree, Frank van (Amsterdam University Press, 1998)
Although vastly influential in German-speaking Europe, conceptual history (Begriffsgeschichte) has until now received little attention in English. This genre of intellectual history differs from both the French history of mentalités and the Anglophone history of discourses by positing the concept - the key occupier of significant syntactical space - as the object of historical investigation. Contributions by distinguished practitioners and critics of conceptual history from Europe and America illustrate both the distinctiveness and diversity of the genre. The first part of the book is devoted to the origins and identity of the field, as well as methodological issues. Part two presents exemplary studies focusing either on a particular concept (such as Maurizio Viroli's 'Reason of the State') or a particular approach to conceptual history (e.g. Bernard Scholz for literary criticism and Terence Ball for political science). The final, most innovative section of the book looks at concepts and art - high, bourgeois and demotic. Here Bram Kempers discusses the conceptual history of Raphael's frescos in the Stanza della Segnatura of the Vatican; Eddy de Jongh examines the linguistic character of much Dutch genre painting; and Rolf Reichardt considers the conceptual structure implicit in card games of the French Revolution, used to induct those on the margins of literacy into the new revolutionary world-view. This title is available in the OAPEN Library - http://www.oapen.org.